2022
DOI: 10.1111/bjh.18089
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic changes in juvenile myelomonocytic leukaemia after treatment with hypomethylating agent: Do they help to evaluate dept of response?

Abstract: Juvenile myelomonocytic leukaemia (JMML) is a rare clonal haematopoietic neoplasm from early childhood with characteristics of both myelodysplastic and myeloproliferative syndromes. It represents 3% of all haematologic malignancies in paediatric patients. [1][2][3] Most patients present mutation of genes of the Rat Sarcoma (RAS) pathway such as the genes tyrosine-protein phosphatase non-receptor type 11 (PTPN11), KRAS proto-oncogene, GTPase (KRAS), NRAS proto-oncogene, GTPase (NRAS), Casitas B-lineage lymphoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“… 20-23 However, in contrast to other hematological malignancies, immunophenotyping is not part of the diagnostic work-up. Despite this, Oliveira et al have recently shown a significant decrease of T lymphocytes and the presence of several phenotypic abnormalities within CD34 + cells of JMML patients including the aberrant expression of CD7 in the majority of CD34 + CD117 + CD13 + cells, associated with a decrease or complete lack of CD19 + CD10 + B-cell precursors, 24 similarly to what has been described in adults with myelodysplastic syndrome (MDS) and/or myeloproliferative neoplasm (MPN). 25 , 26 …”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“… 20-23 However, in contrast to other hematological malignancies, immunophenotyping is not part of the diagnostic work-up. Despite this, Oliveira et al have recently shown a significant decrease of T lymphocytes and the presence of several phenotypic abnormalities within CD34 + cells of JMML patients including the aberrant expression of CD7 in the majority of CD34 + CD117 + CD13 + cells, associated with a decrease or complete lack of CD19 + CD10 + B-cell precursors, 24 similarly to what has been described in adults with myelodysplastic syndrome (MDS) and/or myeloproliferative neoplasm (MPN). 25 , 26 …”
Section: Introductionmentioning
confidence: 70%
“…These aspects are currently being investigated and they may also contribute to a better understanding of the genetic heterogeneity of JMML patients. 24 , 26 , 39 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations